High Dielectric Constant Study of TiO2-Polypyrrole Composites with Low Contents of Filler Prepared by In Situ Polymerization - Khalil Ahmed; Farah Kanwal; Shahid M. Ramay; Asif Mahmood; Shahid Atiq; Yousef S. Al-Zaghayer (Advances in Condensed Matter Physics)
TiO2/polypyrrole composites with high dielectric constant have been synthesized by in situ polymerization of pyrrole in an aqueous dispersion of low concentration of TiO2, in the presence of small amount of HCl. Structural, optical, surface morphological, and thermal properties of the composites were investigated by X-ray diffractometer, Fourier transform infrared spectroscopy, field-emission scanning electron microscopy, and thermogravimetric analysis, respectively. The data obtained from diffractometer and thermal gravimetric analysis confirmed the crystalline nature and thermal stability of the prepared composites. The dielectric constant of 5 wt% TiO2 increased with filler content up to 4.3 × 103 at 1 kHz and then decreased to 1.25 × 103 at 10 kHz.